The rise and fall of the Soviet Union [videorecording] - Baake, Franz; Graves, Peter; Nussabaum, Raphael; Rosinski, Peter (Delta Unique Media VCII Home Entertainment [distributor], 1992)
An epic film that clearly sets forth the dramatic events which occured before during and after the Russian Revolution. It takes the viewer through the First and Second World Wars, the Cold War and through the crumble and collapse of Russia.